2019
DOI: 10.1108/ijshe-09-2018-0149
|View full text |Cite
|
Sign up to set email alerts
|

Promoting green building literacy through online laboratory experiences

Abstract: Purpose This study examines a general education, hands-on and 100 per cent online laboratory course to better understand the prospects for fostering green building literacy through experiential online education. Design/methodology/approach The mixed-methods research design included pre- and post-course surveys (n = 42) together with semi-structured interviews mid-semester (n = 10) and four to six months post-course (n = 5). Data were collected for two semesters. Findings Students experienced significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Students’ preferences were least sustainable in their roles as citizens before the course. Regarding trust in civil organisations and charity, we witnessed a strong positive transformation, which supports the results of Cole et al (2019). However, in terms of product-related donations the authors experienced resistance and no transformation during the semester.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Students’ preferences were least sustainable in their roles as citizens before the course. Regarding trust in civil organisations and charity, we witnessed a strong positive transformation, which supports the results of Cole et al (2019). However, in terms of product-related donations the authors experienced resistance and no transformation during the semester.…”
Section: Discussionsupporting
confidence: 76%
“…Cheng et al (2020) also found a significant change in knowledge, and somewhat weaker but still positive shift in students' attitudes and behaviour towards more sustainable lifestyles. Cole et al (2019) also found evidence for the strengthening of environmental sensitivity and environmentally friendly behaviour.…”
Section: Ijshe 241mentioning
confidence: 86%
See 1 more Smart Citation
“…Particularly, the lack of communication among students and between students and teachers is often stressed, which may result in low student activity during the course, lower learning achievements and higher dropout rates (Anderson et al , 2014; Keržič et al , 2019). On the other hand, several studies prove that e-learning tools can foster learning outcomes and competences (Cole et al , 2019; Förster et al , 2018). Due to greater flexibility, e-learning may better adapt to individual learning styles, for instance by offering either a synchronous and asynchronous learning path (Altomonte et al , 2016;Vaz-Fernandes and Caeiro, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this does not mean that the building can be constructed casually; it is to guarantee the quality and efficiency of the building while minimizing pollution, environmental damage and energy consumption [1][2][3]. In conclusion, green building should be considered comprehensively to improve the importance of nature, people and architecture, to ensure the harmonious coexistence of people and nature, to design the building structure well, to enhance the use of space, and to improve the aesthetics of the building [4]. Green building materials mainly refer to materials with clean production processes, which are often produced from municipal solid waste or industrial and agricultural waste that can be recycled and recycled [5][6].…”
Section: Introductionmentioning
confidence: 99%